Correlation between Attitude of Midwive and Support Cadre in the Behavior of Vitamin a Postpartum Mother Giving Primary Health Center Klaten Region - Hasanah, Intan Nugraheni (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
The Program to prevent vitamin A deficiency in Indonesia includes the administration of vitamin A for post partum mothers by giving a high dose ofvitamin A (@ 200,000 international standard). However, midwives sometimes do not evaluate and follow up the program implantation to make sure thatall postpartum women receive the capsule. This study was aimed at evaluating the midwives’ attitude and health promotors’ support and the behavior ofmidwives in giving the vitamin A capsule to post partum mothers in integrated health center (puskesmas) in Klaten regency. This was a cross-sectionalstudy among 37 midwives in puskesmas of Klaten. The data was obtained using a structured questionnaire. Univariate analysis used frequency distributionand bivariate using chi square test. Most of the respondents (75.6%) had a good supports (68%), there was a correlation between the attitude and behaviorof midwife in giving the vit A capsule (p=0.002). There was a correlation between the support of health promoters with the behavior of midwives in givingvitamin A capsule to post partum mothers(p=0.004). There was a correlation between the attitude and the behavior of midwife and support of healthpromotors and the behavior of midwives in giving the vitamin A to mother in Klaten regency.